ERK activation and autophagy impairment are central mediators of irinotecan-induced steatohepatitis. Issue 11 (4th January 2017) - Mahli, Abdo; Saugspier, Michael; Koch, Andreas; Sommer, Judith; Dietrich, Peter; Lee, Seren; Thasler, Reinhard; Schulze-Luehrmann, Jan; Luehrmann, Anja; Thasler, Wolfgang Erwin; Müller, Martina; Bosserhoff, Anja; et al.
Abstract : Objective: Preoperative chemotherapy with irinotecan is associated with the development of steatohepatitis, which increases the risk of perioperative morbidity and mortality for liver surgery. The molecular mechanisms of this chemotherapeutic complication are widely unknown. Design: Mechanisms of irinotecan-induced steatohepatitis were studied in primary human hepatocytes in vitro, in mice treated with irinotecan and in liver specimens from irinotecan-treated compared with control patients. Results: Irinotecan dose-dependently induced lipid accumulation and pro-inflammatory gene expression in hepatocytes. This was accompanied by an impairment of mitochondrial function with reduced expression of carnitine palmitoyltransferase I and an induction of acyl-coenzyme A oxidase-1 (ACOX1), oxidative stress and extracellular signal-regulated kinase (ERK) activation. ERK inhibition prevented irinotecan-induced pro-inflammatory gene expression but had only a slight effect on lipid accumulation. However, irinotecan also induced an impairment of the autophagic flux mediated by alkalisation of lysosomal pH. Re-acidification of lysosomal pH abolished irinotecan-induced autophagy impairment and lipid accumulation. Also in mice, irinotecan treatment induced hepatic ACOX1 expression, ERK phosphorylation and inflammation, as well as impairment of autophagy and significant steatosis. Furthermore, irinotecan-treated patients revealed higher hepatic ERK activity, expression of pro-inflammatory genes and markers indicative for a shift to peroxisomal fatty acid oxidation and an impaired autophagic flux. Pretreatment with the multityrosine kinase inhibitor sorafenib did not affect autophagy impairment and steatosis but significantly reduced ERK phosphorylation and inflammatory response in irinotecan-treated hepatocytes and murine livers. Conclusions: Irinotecan induces hepatic steatosis via autophagy impairment and inflammation via ERK activation. Sorafenib appears as a novel therapeutic option for the prevention and treatment of irinotecan-induced inflammation.